3t-5=5t-3

Simple and best practice solution for 3t-5=5t-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-5=5t-3 equation:


Simplifying
3t + -5 = 5t + -3

Reorder the terms:
-5 + 3t = 5t + -3

Reorder the terms:
-5 + 3t = -3 + 5t

Solving
-5 + 3t = -3 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
-5 + 3t + -5t = -3 + 5t + -5t

Combine like terms: 3t + -5t = -2t
-5 + -2t = -3 + 5t + -5t

Combine like terms: 5t + -5t = 0
-5 + -2t = -3 + 0
-5 + -2t = -3

Add '5' to each side of the equation.
-5 + 5 + -2t = -3 + 5

Combine like terms: -5 + 5 = 0
0 + -2t = -3 + 5
-2t = -3 + 5

Combine like terms: -3 + 5 = 2
-2t = 2

Divide each side by '-2'.
t = -1

Simplifying
t = -1

See similar equations:

| 0.6(6-0.3n)=-2.1 | | 0.54=0.36m | | -3(x+1)-5(x+1)-6(x-1)=10 | | 42+5x=-2x | | 3x+4+5x+1+2x+5=2x+x+13 | | 10(5)-13(5)= | | =x-x | | AX+3a=3x-17 | | 1=11-11 | | (2a+5b)2-(a+b)(3a-b)= | | 6(2.4+0.4y)-2y=-14 | | c/7+13=36 | | 9u=3u+35 | | 6p^3+1-7p^2=0 | | -14n-q=ft-4n | | 5(-9)+36= | | z^2+(2+2i)z-2i=0 | | x=3.5+0.5(0.46) | | a=-1.967741935 | | 21-15y=14 | | 6p^3-5p^2+1=0 | | 4a-2b=44 | | -3b+3=-5b+2 | | -7.5x+73.8=10.8 | | (21+3y)-3y=14 | | 2x^2+4x+4=40 | | 6(3.5+0.5y)-3y=14 | | 12n-8=13n+18 | | -5+2(x+5)=-5 | | 2x^2+4x+4=36 | | 3.1x-3.9=8.5 | | 34=3(4x+1)-5 |

Equations solver categories